Effect of additives on the performance and morphology of polyethersulfone (PES) blend ultrafiltration membrane - Putri Arina Rohman (2017)
A membrane separation process has become one of emerging technologies that have gained an important place in separation technology and are used in a broad range of applications. However, there are few limitations such as membrane fouling and economic competitive that prevent the membrane reducing the fouling effects. The effects of additives on the Polyethersulfone (PES) membrane performance and also morphology is being investigated throughout this study. Aside from that, the effect of additives on the ability of the membrane to recover from the fouling is also determined in project. The flat membranes were formulated from casting solution of pes polymer, N-methyl-2-pyrrolidone (nmp) solvent, polyethylene glycol (peg) and pluronic F127 additives by immersing them in order to determine their performances which are pure water permeation (pwp), filtration of apple juice and tap water with rejection, flux recovery and reduction, tensile strength and also the morphological structures by membranes prepared with additives contributed to the high flux value during pwp analysis and also high rejection value during the apple juice and tap water filtration. Furthermore, it was found that the additives also able to increase the membranes resistance towards fouling and also the ability of the membrane to recover from the fouling. In summery, it can be concluded that the performance of the membranes could be improved by the addition of polymeric additives.